Features of organizational and technological solutions for the construction and installation of large-span buildings - Tatyana K. Kuzmina; Anton N. Bolshakov; Nadezhda A. Lukyanova; Anastasija V. Puzikova (Нанотехнологии в строительстве)
Introduction. Cable-stayed structures occupy a special place in the modern construction industry due to their unique character istics and wide application possibilities. They allow to convey architectural expression of large span buildings and to ensure high efficiency and minimal weight of structures. Systems with cross arranged cables and arch cable-stayed combined solutions, including "tensegrity" structures, are of particular interest nowadays. Materials and methods. The study is based on an analysis of regulatory documents, scientific and technical literature reflecting the installation of cable-stayed structures, including requirements for the quality of materials, installation processes and structural reliability control. A comparative analysis of various types of cable-stayed systems (parallel, radial and cross arranged) is carried out, and examples of their practical application are considered. Results and discussion. Based on the analysis of regulatory documents and scientific and technical literature review, cable-stayed structures were classified into various categories, reflecting their design features and applications. The advantages and disadvantages of each type of cable-stayed coverings were analyze as well as progressive methods of installations were revealed. Conclusion. The use of cable-stayed coverings, especially with cross-arranged cables and "tensegrity" structures are a promising direction in modern construction. These structures allow to create complex architectural solutions, creating lightweight, aesthetically attractive cover ings. At the same time, the design and installation of cable-stayed structures require consideration of all their disadvantages and limitations to ensure the strength and durability of buildings and structures.